2007
DOI: 10.1038/sj.npp.1301610
|View full text |Cite
|
Sign up to set email alerts
|

Fragile X: Translation in Action

Abstract: Fragile X is a synapsopathy-a disorder of synaptic function and plasticity. Recent studies using mouse models of the disease suggest that the critical defect is altered regulation of synaptic protein synthesis. Various strategies to restore balanced synaptic protein synthesis have been remarkably successful in correcting widely varied mutant phenotypes in mice. Insights gained by the study of synaptic plasticity in animal models of fragile X have suggested novel therapeutic approaches, not only for human fragi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
72
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(73 citation statements)
references
References 25 publications
(25 reference statements)
0
72
1
Order By: Relevance
“…Neuropathological studies of human brain as well as studies in a mouse model of fragile-X syndrome showed that neuronal architecture is abnormal in fragile X syndrome with long, thin and tortuous dendritic spines which appear immature (33). Fragile X syndrome is caused by a loss of function mutation in the fragile-X mental retardation protein (FMRP), an mRNA binding protein that regulates translation (34). In 2002 Huber et al reported that LTD is increased in the hippocampus from mice without FMRP (35).…”
Section: Neuronal Plasticity In Fragile X Syndromementioning
confidence: 99%
“…Neuropathological studies of human brain as well as studies in a mouse model of fragile-X syndrome showed that neuronal architecture is abnormal in fragile X syndrome with long, thin and tortuous dendritic spines which appear immature (33). Fragile X syndrome is caused by a loss of function mutation in the fragile-X mental retardation protein (FMRP), an mRNA binding protein that regulates translation (34). In 2002 Huber et al reported that LTD is increased in the hippocampus from mice without FMRP (35).…”
Section: Neuronal Plasticity In Fragile X Syndromementioning
confidence: 99%
“…A prominent phenotype of the FXS mouse model is increased and stimulusinsensitive protein synthesis, which leads to impairments of several protein synthesis-dependent forms of synaptic plasticity (5,6). To test whether dysregulated protein synthesis in the absence of FMRP can be detected in nonneuronal, peripheral cells from human patients with FXS, we quantified protein synthesis rates in lymphoblastoid cell lines (LCLs) from a healthy control (called "Ctr" in figures and legends) and a patient with FXS that carried the full mutation, that is, completely methylated trinucleotide expansion in the FMR1 gene (subsequently called FXS cells).…”
Section: Dysregulated Protein Synthesis In Fxs Patient Lymphoblastoidmentioning
confidence: 99%
“…A standard curve was used to quantify the amount of phosphatidylinositol (3,4,5) triphosphate present after the reaction.…”
Section: Elisa Pi3k Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Fmr1 knockout, negative regulation is lost leading to enhanced mGlu5 receptor signaling . These studies led to the prediction that mGlu5 receptor antagonists should restore the normal synaptic balance and thus improve behavioral phenotypes (Bear et al, 2008).…”
Section: Intracellular Mglu5mentioning
confidence: 99%